this is what i need to find out: Solve for the x and y intercepts for the rule: (x-6) (x+3)

Roman's answer is correct. Assuming of course that (X - 6)(X + 3) = Y

this is what i need to find out: Solve for the x and y intercepts for the rule: (x-6) (x+3)

Tutors, please sign in to answer this question.

Roman's answer is correct. Assuming of course that (X - 6)(X + 3) = Y

If you want the x intercepts of the equation y = (x - 6)(x + 3) then here they are.

X-intercepts:

Set y = 0 and use the zero product property (if ab = 0 then a = 0 or b = 0)

(x - 6)(x + 3) = 0

x - 6 = 0 or x + 3 = 0.

x = 6 or x = -3

Y-intercept:

Set x = 0.

y = (0 - 3)(0 + 6) = -3*6 = -18